Method for preparing a mixed black powder electrolytic water catalyst and preparation system

CN122898911APending Publication Date: 2026-10-13CHINA UNIV OF MINING & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611360085.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

但是,混合黑粉表面残余PVDF、电解液及含氟有机物会包覆金属氧化物和石墨颗粒,造成浸出速率下降、重构前驱体成核不均以及电催化活性位点被覆盖;铝铜碎屑、隔膜纤维和高分子残渣还会引入非目标杂质,导致热处理过程中活性相烧结或导电网络断裂

Benefits of technology

[0016]有益效果:第一,本发明将微波、超声和臭氧微气泡在净化阶段同步耦合,使微波的选择性活化、超声的机械剥离和臭氧微气泡的强氧化和高传质界面作用于同一颗粒表面,能够在低于传统高温热解的条件下深度去除有机及含氟覆盖物。实施例中有机残留可降至0.20-0.45 wt%,氟残留可降至0.05-0.10 wt%,铝铜附着杂质去除率可达到90%以上,从源头减少后续酸浸和重构的界面阻塞。第二,本发明不是把混合黑粉中的“杂质”全部去除,而是将有害杂质与可利用元素区分处理:聚偏氟乙烯PVDF、电解液残留、隔膜纤维和铝铜碎屑作为杂质排出,Fe、Ni、Co、Mn、P和石墨碳骨架作为催化剂构筑资源保留并重构。该路线能够同时获得锂盐产品和碳负载多元金属催化剂,避免单纯湿法回收后再外购金属盐制备催化剂造成的流程拉长。第三,选择性浸出与结构重构在同一元素链条中完成。深度净化后的颗粒表面更亲液,酸浸过程中Li的液相进入比例可达到95%以上,Fe、Ni、Co、Mn等进入重构体系的比例可达到88%—96%;石墨碳骨架回配使过渡金属物种在原位碳载体上成核,避免游离沉淀带来的大颗粒团聚。第四,气相渗透热解使含磷气相或含硫气相从气相均匀穿透前驱体床层,能够形成5-30 nm的多元金属磷化物、金属硫化物或其复合相纳米晶,并同步获得N、S、P中至少一种杂原子掺杂碳网络。与直接固相混合磷化或硫化相比,气相渗透可降低局部高浓度反应导致的烧结,改善电解水反应中的电子传导和电解液可达性。第五,本发明的催化剂在1 mol/L KOH中达到10 mA/cm2时,析氧反应过电位可低至248 mV -270mV,析氢反应过电位可低至132 mV -150 mV,OER Tafel斜率可低至61 mV/dec -72 mV/dec,HER Tafel斜率可低至84 mV/dec -98 mV/dec,双电层电容Cdl可达16.8 mF/cm2-22.4mF/cm2;两电极全水分解达到10 mA/cm2所需槽电压可低至1.58 V -1.63 V,并可在50h-100 h恒流和恒压稳定性测试中保持较小衰减,体现了所述组合工艺在杂质去除率、浸出率、活性位点暴露和催化稳定性上的协同优势。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898911A_ABST
    Figure CN122898911A_ABST
Patent Text Reader

Abstract

The application discloses a method and a preparation system for preparing an electrolytic water catalyst from mixed black powder, and belongs to the technical field of resource utilization of waste lithium ion batteries and preparation of new energy electrocatalytic materials. Microwave-ultrasonic-ozone micro-bubble synergy deep purification is performed, impurities are removed at low temperature, and graphite carbon skeletons and Fe, Ni, Co, Mn and P target elements are reserved; element controllable leaching and structure reconstruction enable Li to enter a mother liquor for lithium salt recovery; gas phase permeation pyrolysis and directional conversion simultaneously complete at least one of carbonization, phosphorization and sulfidation and heteroatom doping, so that a heteroatom doped carbon loaded multi-metal phosphide, sulfide or composite phase electrolytic water catalyst is obtained. The harmful impurities are removed, lithium salt is recovered, transition metal is reconstructed and graphite carbon skeletons are high-value utilized in series coupling, the impurity removal rate is high, the element leaching rate is high, the electrolytic water catalyst performance is good, and the application is suitable for resource treatment of lithium iron phosphate, ternary materials and industrial mixed black powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of resource utilization technology for waste lithium-ion batteries, specifically to a method and preparation system for preparing a water electrolysis catalyst by mixing black powder. Background Technology

[0002] The mixed black powder obtained from the discharge, dismantling, crushing, and sorting of waste lithium-ion batteries typically consists of positive electrode active materials, negative electrode graphite, conductive carbon, polyvinylidene fluoride binder, residual electrolyte, SEI and CEI membrane components, and aluminum and copper foil fragments. The composition of industrially sourced black powder varies greatly, often containing lithium iron phosphate, ternary materials, lithium cobalt oxide, lithium manganese oxide, and graphite systems simultaneously. If a single-system wet recycling process is used, it usually requires multi-stage acid leaching, separation, purification, and resynthesis, resulting in a long process and limited added value.

[0003] Directly converting black powder into a water electrolysis catalyst allows for the simultaneous utilization of transition metals, phosphorus, and the graphite carbon skeleton, representing an important direction for enhancing resource utilization value. However, residual PVDF, electrolyte, and fluorine-containing organic matter on the surface of the mixed black powder can coat metal oxides and graphite particles, causing a decrease in leaching rate, uneven nucleation of reconstructed precursors, and coverage of electrocatalytic active sites. Aluminum and copper debris, membrane fibers, and polymer residues can also introduce non-target impurities, leading to sintering of the active phase or breakage of the conductive network during heat treatment.

[0004] In existing technologies, units such as ultrasound, ozone microbubbles, microwave acid leaching, solvothermal reconstruction, or phosphating or sulfidation heat treatment have their own applications. However, common processes mostly aim at metal salt recovery or simply calcine black powder into mixed oxides, failing to form a continuous technology chain of "selective removal of harmful substances, retention of usable elements, reconstruction of the active phase on the original graphite carbon framework, and then directional conversion through gas-phase permeation." Therefore, a method is needed that can clearly distinguish between harmful impurities and usable elements and demonstrate that synergistic purification has a combined effect on improving leaching rate, reconstruction uniformity, and catalytic performance. Summary of the Invention

[0005] Technical Problem: To address the shortcomings of existing technologies, a method and system for preparing water electrolysis catalysts by mixing black powders are provided. Through deep purification of "removing harmful substances and retaining them" and directional conversion of "leaching-recombining-reconstruction-gas phase permeation", lithium is recovered in the form of salt. At the same time, Fe, Ni, Co, Mn, P and graphite carbon skeleton are converted into high-performance water electrolysis catalysts. The steps are simple and the effect is good.

[0006] To achieve the above technical objectives, this invention discloses a method for preparing an electrolytic water catalyst by mixing black powder, comprising the following steps: S1. Mix the black powder with water to form a slurry, and then perform microwave-ultrasound-ozone microbubble synergistic deep purification to obtain purified powder that retains the graphite carbon skeleton and the target metal. S2. The purified powder is subjected to controllable leaching of the target elements in a controllable acid system, and then solid-liquid separation is performed to obtain a solid phase containing a graphite carbon skeleton and a leachate containing lithium ions and transition metal ions, respectively. S3. The solid phase containing the graphite carbon skeleton is returned to the leaching solution or the transition metal enriched portion obtained by the leaching solution through regulation, and in-situ structural reconstruction is carried out to form a composite precursor supported by the graphite carbon skeleton; and lithium salt is recovered from the lithium-containing mother liquor after the composite precursor is separated. S4. The composite precursor is placed in an inert atmosphere for pyrolysis, and at least one of pyrolytic carbonization, metal phosphating and sulfidation occurs, as well as heteroatom doping of the graphite carbon framework, to obtain an electrolytic water catalyst with heteroatom-doped graphite carbon framework supporting multi-metal compounds.

[0007] Furthermore, in S1, the mixed black powder is a mixture of positive and negative electrode active materials obtained from waste lithium-ion batteries through discharge, dismantling, crushing and sorting, including at least one of lithium iron phosphate system black powder, ternary system black powder, lithium cobalt oxide system black powder and lithium manganese oxide system black powder; The process of microwave-ultrasound-ozone microbubble synergistic deep purification is as follows: the mixed black powder obtained by crushing and sieving is dispersed in water, and under the simultaneous action of microwave bulk heating, ultrasonic cavitation stripping and ozone microbubble strong oxidation mass transfer, the polyvinylidene fluoride binder, residual electrolyte, SEI membrane and CEI membrane components, fluorine-containing organic derivatives, membrane fibers and fine impurities attached to aluminum foil and copper foil on the surface of the mixed black powder are removed, and purified powder retaining the graphite carbon skeleton and one or more target elements of Fe, Ni, Co, Mn and P is obtained.

[0008] Furthermore, in S1, the black powder and water are mixed into a slurry at a mass-volume solid-liquid ratio of 1g:(10-30)mL; In the synergistic deep purification process of microwave-ultrasound-ozone microbubble, the microwave power is 300W-800W, and it operates in continuous or pulsed mode; the average diameter of the ozone microbubbles is no greater than 50 mm. The ozone concentration was 50 mg / L-120 mg / L; the ultrasonic frequency was 20 kHz-40 kHz; the ultrasonic power was 100 W-500 W; the reaction temperature was 60 ℃-120 ℃; the reaction time was 0.5 h-2 h; and the redox potential of the system was controlled at 700 mV-1100 mV. In this process, ozone microbubbles enter the slurry from the bottom of the reactor. An ultrasonic probe, used for ultrasonic treatment, is positioned below the slurry surface and overlaps with the rising area of ​​the ozone microbubbles. Microwave radiation selectively heats the organic-coated particles in the slurry. The foamy light phase and cleaning fluid formed during the purification process carry PVDF-decomposed small molecules... Hydrolysis and oxidation products, membrane fibers, and aluminum and copper particles are discharged, thereby reducing mass transfer resistance in subsequent leaching and remodeling steps.

[0009] Furthermore, in S2, the controllable acid system is sulfuric acid, hydrochloric acid, nitric acid, citric acid, oxalic acid, malic acid, or a mixture of the above acids, with an acid concentration of 0.2 mol / L-1.5 mol / L, and the leaching temperature is... The leaching time is 0.5h-2h, and the pH at the leaching endpoint is 1.5-2.5. The controlled leaching using a controllable acid system ensures that the proportion of lithium ions entering the liquid phase is not less than 90%, and the retention rate of the graphite carbon skeleton is not less than 80%. The transition metal ions included in the leaching process are lithium ions and transition metal ions, including one or more of Fe, Ni, Co, and Mn.

[0010] Further, S3 specifically involves: returning the solid phase containing the graphite carbon framework obtained in step S2 to the leachate or the transition metal enrichment portion; the transition metal enrichment portion is: a liquid phase or wet precipitate phase in which one or more ions of Fe, Ni, Co, and Mn are relatively enriched, obtained from the leachate by adjusting the pH to 4.5-8.5, adding a complexing agent, adding a precipitant, ion exchange, or electrochemical enrichment. After the recombination is completed, nitrogen-containing ligands, sulfur-containing ligands and structure-directing agents are added to enable transition metal species to grow in situ on the surface and pores of the graphite carbon framework as metal-organic frameworks, layered double hydroxides, metal hydroxides, metal phosphates or their complex precursors. Lithium carbonate can be recovered by adding sodium carbonate, sodium bicarbonate, ammonium carbonate, or introducing carbon dioxide to the lithium-containing mother liquor after separating the composite precursor for carbonization precipitation.

[0011] Furthermore, the nitrogen-containing ligand is one or more of 2-methylimidazole, urea, melamine, dicyandiamide, or polyvinylpyrrolidone, and the sulfur-containing ligand is one or more of thiourea, thioacetamide, p-aminobenzenesulfonic acid, or dibenzyl disulfide; the structure-directing agent is one or more of hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, polyvinylpyrrolidone, polyethylene glycol, polyethyleneimine, Pluronic F127, Pluronic P123, citric acid, or sodium citrate; the structure-directing agent is used to regulate the nucleation density, lamellar orientation, particle size, or porous shell structure of transition metal species on the surface and within the pores of the graphite carbon framework; the structure reconstruction temperature is 120℃-180℃, and the time is 6h-24h, so that the metal species grow in situ on the surface and within the pores of the graphite carbon framework in the form of nanosheets, nanoparticles, or porous shells.

[0012] Furthermore, the composite precursor formed by in-situ structural reconstruction is pyrolyzed in an inert atmosphere; simultaneously, a phosphorus-containing gas phase is generated by independently heating at least one of sodium hypophosphite, triphenylphosphine, and red phosphorus, and / or a sulfur-containing gas phase is generated by independently heating sulfur powder, thiourea, or an organic sulfur source, and the phosphorus-containing gas phase and / or sulfur-containing gas phase are permeated through the composite precursor by a carrier gas, causing the composite precursor to carbonize and undergo at least one of phosphating and sulfidation, while simultaneously doping with at least one heteroatom of N, S, and P, forming nano-multi-element metal phosphides, metal sulfides, metal oxides, and composite phases formed by at least two of metal oxides, metal sulfides, and metal phosphides, and the active phase is uniformly loaded on the graphite carbon framework; The pyrolysis temperature is 700℃~900℃, the heating rate is 2℃ / min~10℃ / min, the holding time is 1h~4h, the carrier gas is argon or nitrogen, and the flow rate is 30mL / min~200mL / min.

[0013] An electrolytic water catalyst prepared by a method of mixing black powder comprises a carbon network doped with at least one heteroatom of N, S, and P, and an active phase supported on the carbon network. The active phase is one of metal phosphides, metal sulfides, and metal oxides, or a composite phase formed from at least two of metal phosphides, metal sulfides, and metal oxides; the metal phosphides include... , or Metal sulfides include , or The average particle size of the active phase is 5nm-30nm, and at least part of the active phase is coated with 1-5 layers of graphitized carbon shell.

[0014] A preparation system for a method of preparing an electrolytic water catalyst by mixing black powder includes a purification unit, a first solid-liquid separation unit, a selective leaching-structure reconstruction unit, a second solid-liquid separation unit, a gas phase permeation pyrolysis unit, and a tail gas absorption unit connected in sequence, and includes a control unit connected to each of the above units. The purification unit includes a reactor with temperature control and a microwave emitting device on the side of the reactor. A temperature controller is installed on the side wall of the reactor, with the reactor outlet above the temperature controller and the reactor inlet below the temperature controller. An oxidation-reduction potential detection device is installed inside the reactor, and an ultrasonic probe that extends vertically into the reaction chamber is installed on the top cover of the reactor. A bubble outlet with a shower-like structure and an upward-facing outlet is installed at the bottom of the reactor. The bubble outlet is sequentially connected to a microbubble generator and an ozone generator through pipelines. The end of the ultrasonic probe overlaps with the rising area of ​​the ozone microbubbles generated by the bubble outlet. The gas-phase permeation pyrolysis unit includes a furnace body, a heat-resistant reaction tube penetrating the furnace body, a carrier gas inlet, a gas phase source zone located upstream of the carrier gas, a precursor pyrolysis zone located downstream of the gas phase source zone, a furnace temperature control unit, and a condensation absorption zone connected to the outlet of the heat-resistant reaction tube; the gas phase source zone, the precursor pyrolysis zone, and the condensation absorption zone are connected sequentially along the direction of carrier gas flow.

[0015] Furthermore, the solid phase outlet of the first solid-liquid separation unit is connected to the selective leaching-structural reconstruction unit, the liquid phase outlet of the second solid-liquid separation unit is connected to the lithium salt recovery unit, and the solid phase outlet of the second solid-liquid separation unit is connected to the gas phase permeation pyrolysis unit; the control unit controls the microwave power, ultrasonic power, ozone flow rate, pH, redox potential, acid leaching endpoint, carrier gas flow rate, and pyrolysis temperature in a coordinated manner.

[0016] Beneficial effects: First, this invention simultaneously couples microwaves, ultrasound, and ozone microbubbles during the purification stage. This allows the selective activation of microwaves, the mechanical stripping of ultrasound, and the strong oxidation and high mass transfer interface of ozone microbubbles to act on the same particle surface, enabling deep removal of organic and fluorine-containing coatings under conditions lower than traditional high-temperature pyrolysis. In the examples, organic residues can be reduced to 0.20-0.45 wt%, fluorine residues to 0.05-0.10 wt%, and the removal rate of aluminum and copper adhering impurities can reach over 90%, reducing interface blockage during subsequent acid leaching and reconstruction from the source. Second, this invention does not remove all "impurities" from the mixed black powder, but rather distinguishes between harmful impurities and usable elements: polyvinylidene fluoride (PVDF), electrolyte residues, membrane fibers, and aluminum and copper debris are discharged as impurities, while Fe, Ni, Co, Mn, P, and graphite carbon skeletons are retained and reconstructed as catalyst building resources. This route can simultaneously obtain lithium salt products and carbon-supported multi-metal catalysts, avoiding the process lengthening caused by simply recovering the metals through wet processes and then purchasing them to prepare catalysts. Third, selective leaching and structural reconstruction are completed within the same elemental chain. The deeply purified particle surface is more hydrophilic; during acid leaching, the liquid phase entry rate of Li can reach over 95%, while the entry rates of Fe, Ni, Co, Mn, etc., into the reconstruction system can reach 88%–96%. The re-allocation of the graphite carbon framework allows transition metal species to nucleate in situ on the carbon support, avoiding large particle agglomeration caused by free precipitation. Fourth, gas-phase infiltration pyrolysis allows phosphorus- or sulfur-containing gas phases to uniformly penetrate the precursor bed from the gas phase, forming 5–30 nm multi-element metal phosphides, metal sulfides, or their composite phase nanocrystals, and simultaneously obtaining a carbon network doped with at least one heteroatom from N, S, or P. Compared to direct solid-phase mixed phosphating or sulfidation, gas-phase infiltration can reduce sintering caused by localized high-concentration reactions and improve electron conduction and electrolyte accessibility in the water electrolysis reaction. Fifth, when the catalyst of this invention reaches 10 mA / cm² in 1 mol / L KOH, the oxygen evolution reaction overpotential can be as low as 248 mV - 270 mV, the hydrogen evolution reaction overpotential can be as low as 132 mV - 150 mV, the OER Tafel slope can be as low as 61 mV / dec - 72 mV / dec, the HER Tafel slope can be as low as 84 mV / dec - 98 mV / dec, and the double-layer capacitance Cdl can reach 16.8 mF / cm² - 22.4 mF / cm². The cell voltage required for two-electrode total water splitting to reach 10 mA / cm² can be as low as 1.58 V - 1.63 V, and it can maintain a small decay in constant current and constant voltage stability tests over 50 h - 100 h, demonstrating the synergistic advantages of the combined process in terms of impurity removal rate, leaching rate, active site exposure, and catalytic stability. Attached Figure Description

[0017] Figure 1This is a schematic flowchart of the method for preparing an electrolytic water catalyst by mixing black powder according to the present invention.

[0018] Figure 2 This is a schematic diagram of the purification unit in an embodiment of the present invention; Figure 3 This is a schematic diagram of the overall preparation system for preparing an electrolytic water catalyst using mixed black powder in an embodiment of the present invention.

[0019] In the diagram: 1. Microwave transmitter, 2. Ozone generator, 3. Microbubble generator, 4. Ultrasonic probe, 5. Reactor, 6. Water outlet, 7. Temperature controller, 8. Water inlet, 9. Bubble outlet. Detailed Implementation

[0020] The embodiments of the present invention will be further described below with reference to the accompanying drawings.

[0021] like Figure 1 As shown, this invention discloses a method for preparing an electrolytic water catalyst by mixing black powder, the steps of which are as follows: Step 1: Deep purification through microwave-ultrasound-ozone microbubble synergistic process. Add the mixed black powder and deionized water to the purification unit (e.g., Figure 2 A slurry is formed in the solution (as shown), and microwave, ultrasonic, and ozone microbubble processes are initiated. Microwaves provide bulk heating and selective activation of PVDF containing polar bonds, electrolyte residues, and SEI and CEI films. Ultrasonic cavitation generates microjets to peel off the surface coating of particles. Ozone microbubbles, under ultrasonic action, form a high-contact-area oxidation interface, promoting chain breakage, oxidation, and desorption of the organic coating. After treatment, foam is discharged, solid-liquid separation is performed, followed by washing and drying to obtain purified powder. The purification process does not remove all metal elements, but prioritizes the removal of PVDF binder, carbonate electrolyte residues, LiPF6 hydrolysis products and oxidized fluorine-containing products, the SEI film at the solid electrolyte interface and the CEI film at the positive electrode electrolyte interface, membrane fibers, and aluminum and copper adhering impurities, while retaining the graphite carbon skeleton and target elements: Fe, Ni, Co, Mn, and P.

[0022] The solid-liquid ratio of the mixed black powder to deionized water is 1 g:(10-30) mL. The microwave power is 300 W-800 W, the ultrasonic frequency is 20 kHz-40 kHz, the ultrasonic power is 100 W-500 W, the average diameter of the ozone microbubbles is no greater than 50 μm, the ozone concentration is 50 mg / L-120 mg / L, the treatment temperature is 60℃-120℃, and the treatment time is 0.5 h-2 h. The microwave can be operated continuously or in pulsed mode.

[0023] Step two, controlled leaching and structural reconstruction. The purified powder is added to a controlled acid system for gentle leaching. The acid concentration, temperature, and final pH are controlled to allow lithium ions to enter the liquid phase, and at least one transition metal ion from Fe, Ni, Co, and Mn to enter the leaching solution or the transition metal-enriched portion or wet precipitate obtained through pH adjustment, complexation, and fractional precipitation, while the graphite carbon framework remains largely in the solid phase. Subsequently, the graphite carbon framework is returned to the leaching solution, the transition metal-enriched portion, or the wet precipitate, and nitrogen-containing ligands, sulfur-containing ligands, and structure-directing agents are added to allow transition metal species to grow in situ on the surface and pores of the graphite carbon framework as metal-organic frameworks (MOFs), layered bimetallic hydroxides (LDHs), metal hydroxides, metal phosphates, or their composite precursors. The transition metal-enriched portion refers to the liquid phase or wet precipitate obtained from the leaching solution through pH adjustment, complexation, precipitation, ion exchange, or electrochemical enrichment, where transition metal ions such as Fe, Ni, Co, and Mn are relatively enriched.

[0024] The purpose of re-mixing is to use the original black powder graphite as a conductive framework and nucleation carrier, so that at least one metal element from the black powder, such as Fe, Ni, Co, and Mn, as well as phosphorus, are redistributed and fixed on the graphite carbon framework, rather than simply precipitating as free metal salts.

[0025] The controllable acid system includes sulfuric acid, hydrochloric acid, nitric acid, citric acid, oxalic acid, malic acid, or combinations thereof, with a leaching endpoint pH of 1.5-2.5. The transition metal enrichment portion refers to the liquid or wet precipitate phase in which Fe, Ni, Co, and Mn ions are relatively enriched, obtained from the leachate through pH adjustment, complexation, precipitation, ion exchange, or electrochemical enrichment. Nitrogen-containing ligands include one or more of 2-methylimidazolium, urea, melamine, dicyandiamide, or polyvinylpyrrolidone; sulfur-containing ligands include one or more of thiourea, thioacetamide, p-aminobenzenesulfonic acid, or dibenzyl disulfide; the structure-directing agent includes one or more of hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, polyvinylpyrrolidone, polyethylene glycol, polyethyleneimine, Pluronic F127, Pluronic P123, citric acid, or sodium citrate; the solvothermal reaction temperature is 120℃-180℃, and the reaction time is 6 h-24 h. After solid-liquid separation, the lithium-containing mother liquor is added with sodium carbonate, sodium bicarbonate, ammonium carbonate, or carbonized with carbon dioxide to precipitate lithium as lithium carbonate. After aging, filtration, washing, and drying, the lithium salt product is obtained.

[0026] When the graphite carbon skeleton is reconstituted into a lithium-containing leaching solution for reconstruction, most of the lithium ions do not enter the precursor solid phase, but remain in the reconstituted mother liquor, ensuring the subsequent recovery rate of lithium salts and the purity of the precursor.

[0027] Step 3: Gas-phase infiltration pyrolysis and directional conversion. The reconstructed composite precursor is placed in the precursor zone of a tubular furnace or continuous pyrolysis furnace. The gas-phase source zone is located upstream of the carrier gas. Phosphorus-containing or sulfur-containing gas phases are generated by heating sodium hypophosphite, triphenylphosphine, red phosphorus, sulfur powder, thiourea, or organic sulfur sources. Driven by Ar or N2 carrier gas, the phosphorus-containing or sulfur-containing gas phases infiltrate through the precursor bed, causing carbonization of the precursor and at least one of phosphating and sulfidation. Simultaneously, at least one heteroatom of N, S, and P is doped, forming nano-multi-element metal phosphides, metal sulfides, metal oxides, and composite phases formed from at least two of metal oxides, metal sulfides, and metal phosphides. The active phases are uniformly loaded onto the graphite carbon framework. The gas-phase infiltration method avoids localized overreaction and sintering agglomeration caused by direct mixing of solid phosphorus or sulfur sources with the precursor.

[0028] The precursor region temperature is 700℃-900℃, the heating rate is 2℃ / min-10℃ / min, the holding time is 1 h-4 h, and the carrier gas flow rate is 30 mL / min-200 mL / min; the average particle size of the active phase of the obtained catalyst is 5 nm-30 nm, and at least part of the active phase is coated by a graphitized carbon shell.

[0029] like Figure 3As shown, in the preparation system for preparing an electrolytic water catalyst using mixed black powder, the slurry outlet of the purification unit is connected to the first solid-liquid separation unit. The first solid-liquid separation unit is an acid-resistant filter, centrifuge, plate and frame filter press, or membrane filtration device. The solid phase outlet of the first solid-liquid separation unit is connected to the selective leaching-structure reconstruction unit. The liquid phase or foam light phase outlet of the first solid-liquid separation unit is connected to the cleaning liquid and foam light phase treatment end. The selective leaching-structure reconstruction unit is an acid-resistant reactor, hydrothermal reactor, or solvothermal reactor equipped with stirring, heating, pH detection, redox potential detection, and a dosing port. The selective leaching-structure reconstruction unit receives acid, complexing agent, precipitant, nitrogen-containing ligand, sulfur-containing ligand, and structure-directing agent through a reagent storage tank and a dosing pump. Its outlet is connected to the second solid-liquid separation unit. The second solid-liquid separation unit is a centrifuge, filter, or filter press. The solid phase outlet of the first solid-liquid separation unit is connected to the precursor region of the gas-phase permeation pyrolysis unit, and the liquid phase outlet of the second solid-liquid separation unit is connected to the lithium salt recovery unit. The lithium salt recovery unit includes a precipitation reactor, an aging tank, a filtration and washing device, and a drying device, used to prepare lithium salt products from lithium-containing mother liquor. The gas-phase permeation pyrolysis unit is a tubular furnace, a rotary furnace, or a continuous pyrolysis furnace, and its tail gas outlet is connected to a condensation or tail gas absorption unit, which is a condenser, an alkaline absorption bottle, or a packed absorption tower. The control unit is a PLC or an industrial computer control cabinet, and is electrically or signal-connected to the purification unit, the first solid-liquid separation unit, the selective leaching-structural reconstruction unit, the second solid-liquid separation unit, the lithium salt recovery unit, and the gas-phase permeation pyrolysis unit, respectively, for linkage control of microwave power, ultrasonic power, ozone flow rate, pH, oxidation-reduction potential, acid leaching endpoint, carrier gas flow rate, and pyrolysis temperature.

[0030] The following examples are used to illustrate the technical solutions of the present invention, but do not limit the scope of protection of the present invention. Unless otherwise stated, the percentages are mass percentages; the following electrochemical test conditions and evaluation methods are as follows.

[0031] (1) Three-electrode activity test: 5 mg of catalyst was weighed and added to 950 μL of isopropanol / water mixed solvent (volume ratio 1:1) and 50 μL of 5 wt% Nafion solution. The catalyst slurry was ultrasonically dispersed for 30 min to obtain a catalyst slurry. The catalyst slurry was drop-coated onto the glassy carbon electrode or carbon paper working area. After drying, the catalyst loading was 0.5 mg / cm². 2 The electrolyte was 1 mol / L KOH. The OER test used a Hg / HgO reference electrode and a graphite rod as the counter electrode, while the HER test used a Hg / HgO reference electrode and a graphite rod or platinum sheet as the counter electrode. N2 was introduced for 20 min before the test. The linear sweep voltammetry (LSV) scan rate was 5 mV / s. The potential was converted to the RHE scale (reversible hydrogen electrode scale) and corrected by iR (ohmic drop compensation).

[0032] (2) Kinetics and active area evaluation: The Tafel slope was obtained by fitting the iR-corrected LSV polarization curve in the linear kinetic region. C dl (Electrochemical double-layer capacitance) was calculated using CV curves at different scan rates (10, 20, 30, 40, 50 mV / s) within the non-Radida interval. The difference between the anodic and cathodic current densities was used to linearly fit the scan rate. ECSA (electrochemical active surface area of ​​the catalyst) was calculated using ECSA=C dl / Cs estimation, where Cs is taken as 40 μF / cm 2 .

[0033] (3) Two-electrode total water splitting and stability test: The same catalyst was coated on nickel foam or carbon paper as the anode and cathode, respectively. The electrolyte was 1 mol / L KOH and the electrode geometric area was 1 cm². 2 Recording reached 10 mA / cm 2 Required tank voltage. Constant current stability test at 10 mA / cm². 2 The system continuously runs and records the tank voltage increment; the constant voltage current stability test initially reaches 10 mA / cm. 2 The system operates continuously under the specified tank voltage, and the change in current density over time is recorded. The current density retention rate is calculated as (final current density / initial current density) × 100%. The higher the retention rate, the smaller the electrode activity decay under the same tank voltage.

[0034] Example 1: 10 g of lithium iron phosphate / graphite mixed black powder, with Fe mass fraction of 18 wt%, P mass fraction of 6 wt%, and C mass fraction of 30 wt%, was taken. The black powder, 200 mL of deionized water, and 0.01 g of FeSO4 were added to the purification unit, and the pH of the slurry was adjusted to 5.0. The microwave power was set to 500 W and operated in a 10 s on / 10 s off pulse mode. The ultrasonic frequency was set to 40 kHz and the ultrasonic power to 300 W. Simultaneously, ozone microbubbles were introduced from the bottom of the reactor at an ozone concentration of 100 mg / L, with an average bubble diameter not exceeding 50 μm. The reaction temperature was 90℃, and the treatment time was 60 min. After the reaction, the foamy light phase was discharged, filtered, washed with water, and dried at 80℃ to obtain the purified powder. Thermogravimetric analysis, ion chromatography, and ICP analysis showed that the organic matter removal rate of the original black powder was 99.1%; the fluorine residue was 0.06 wt%; the removal rate of aluminum and copper adhering impurities was 92.5%; and the graphite carbon skeleton retention rate was 91.0%.

[0035] The purified powder was added to a 0.5 mol / L H₂SO₄ solution at a solid-liquid ratio of 1 g: 15 mL, and leached at 50 °C for 60 min, with the final pH controlled at 2.0. The leachate and a graphite carbon framework-enriched solid phase were obtained by filtration. ICP testing showed that Li entered the liquid phase at a rate of 96.5%, while Fe and P entered the reconfigurable system at rates of 90.2% and 88.5%, respectively. The graphite carbon framework-enriched solid phase was recombined into the transition metal enriched portion of the leachate, and 2.0 g of 2-methylimidazole, 1.0 g of thiourea, and 0.5 g of urea were added. The mixture was then solvothermal reacted at 160 °C for 12 h to obtain an Fe-based precursor / carbon composite material. The lithium-containing mother liquor after precursor solid-liquid separation was heated to 90 °C, sodium carbonate solution was added, and the mixture was aged for 1 h. After filtration, washing, and drying, lithium carbonate was obtained. The overall lithium recovery rate was 91.5%, and the purity of lithium carbonate was 98.5%.

[0036] The obtained Fe-based precursor / carbon composite material was placed in the precursor zone of a tube furnace, and sodium hypophosphite was placed in the upstream gas source zone. Ar gas was introduced at a flow rate of 80 mL / min. The temperature was increased to 800℃ at 5℃ / min and held for 2 h. Simultaneous heating in the gas source zone generated a phosphorus-containing gas phase, which permeated through the precursor bed. After cooling, the catalyst was washed with 0.5 mol / L H₂SO₄, water, and dried to obtain the FeP@N,S,PC catalyst. TEM (transmission electron microscopy) and XRD (X-ray diffraction) characterization showed that the average particle size of the active phase was approximately 12 nm, with some nanocrystals coated with 2-4 layers of graphitized carbon shell. Electrochemical tests showed that at 10 mA / cm², the catalyst exhibited good performance. 2 The overpotential of OER was 260 mV, and the overpotential of HER was 145 mV. The Tafel slopes of OER and HER were 68 mV / dec and 92 mV / dec, respectively. dl It is 18.6 mF / cm 2 Corresponding to ECSA approximately 465 cm 2 The catalyst was used as both the anode and cathode in a two-electrode system, achieving a flux of 10 mA / cm². 2 The required tank voltage is 1.63 V, at 10 mA / cm². 2 After 100 hours of continuous operation under constant current, the cell voltage increment was 28 mV, and after 100 hours of continuous operation under constant cell voltage of 1.63 V, the current density retention rate was 93%.

[0037] Example 2: 10 g of ternary cathode material / graphite mixed black powder was taken, wherein the mass fraction of Ni was 12 wt%, the mass fraction of Co was 8 wt%, the mass fraction of Mn was 6 wt%, and the mass fraction of C was 25 wt%. It was treated according to the triple purification route of Example 1, except that the microwave power was 600 W, the ozone concentration was 110 mg / L, and the treatment temperature was 95℃. After treatment, thermogravimetric analysis, ion chromatography, and ICP detection showed that the organic matter removal rate of the original black powder was 99.3%; the fluorine residue was 0.05 wt%; and the removal rate of aluminum and copper adhering impurities was 94.0%.

[0038] The purified powder was leached in a 0.75 mol / L H₂SO₄ system at 60 °C for 60 min, with a final pH of 2.0. After leaching, solid-liquid separation was performed, and the graphite carbon skeleton-enriched solid phase was recombined into the Ni, Co, and Mn-enriched fraction. 2-Methylimidazole, thiourea, and urea were added, and the mixture was solvothermal reacted at 170 °C for 12 h to obtain the NiCoMn precursor / carbon composite material. In this step, the proportions of Li, Ni, Co, and Mn entering the liquid phase or reconstructing the system were 97.2%, 96.0%, 95.4%, and 92.8%, respectively, with a graphite carbon skeleton retention rate of 88.5%. The overall lithium recovery rate after lithium salt recovery was 92.0%.

[0039] A NiCoMn precursor / carbon composite material was placed in a gas-phase permeation pyrolysis furnace, using triphenylphosphine vapor as the gaseous phosphorus source. The temperature was increased to 820℃ at 5℃ / min under an Ar atmosphere and held for 2 h to obtain a NiCoMnP@N,S,PC catalyst. The average particle size of the active phase of this catalyst was approximately 10 nm. In 1 mol / L KOH, a flux of 10 mA / cm² was achieved. 2 The overpotential of OER was 248 mV, and the overpotential of HER was 132 mV. The Tafel slopes of OER and HER were 61 mV / dec and 84 mV / dec, respectively. dl It is 22.4 mF / cm 2 The corresponding ECSA (electrochemically active area) is approximately 560 cm². 2 The total water splitting efficiency at both electrodes reached 10 mA / cm². 2 The slot voltage is 1.58 V, at 10 mA / cm 2 After 80 hours of continuous operation under constant current, the cell voltage increment was 32 mV, and after 80 hours of continuous operation under a constant cell voltage of 1.58 V, the current density retention rate was 95%.

[0040] Example 3: 10 g of industrial mixed black powder, containing lithium iron phosphate, ternary materials, and graphite, was taken. The total mass fraction of Fe, Ni, Co, and Mn was 21 wt%, and the mass fraction of C was 28 wt%. Synergistic deep purification was performed under the conditions of microwave power 500 W, ultrasonic power 300 W, ozone concentration 100 mg / L, 90℃, and 60 min. After purification, thermogravimetric analysis, ion chromatography, and ICP analysis showed that the organic matter removal rate of the original black powder was 98.4%; the fluorine residue was 0.10 wt%; and the removal rate of aluminum and copper adhering impurities was 90.8%. Subsequently, leaching was carried out in a 0.6 mol / L sulfuric acid-citric acid composite acid system, with the pH controlled at 2.1. The proportion of Li entering the liquid phase was 95.0%, the combined proportion of Fe, Ni, Co, and Mn entering the reconstruction system was 90.5%, and the graphite carbon skeleton retention rate was 86.8%.

[0041] The reconstructed multimetal precursor / carbon composite material was pyrolyzed at 800 °C for 2 h in phosphorus-containing and sulfur-containing gas phases provided by sulfur powder vapor and sodium hypophosphite, respectively, to obtain a FeNiCoMn phosphorus-sulfur composite phase@N,S,PC composite catalyst. (The last part, "10 mA / cm³", appears to be an unrelated instruction and is omitted from the translation.) 2 The overpotential of OER is 270 mV, and the overpotential of HER is 150 mV. The Tafel slopes of OER and HER are 72 mV / dec and 98 mV / dec, respectively; C dl It is 16.8 mF / cm 2 Corresponding to ECSA approximately 420 cm 2 The voltage in the two-electrode total water splitting cell was 1.63V, at 10 mA / cm². 2 After 50 hours of continuous operation under constant current, the cell voltage increment was 41 mV, and after 50 hours of continuous operation under a constant cell voltage of 1.63 V, the current density retention rate was 92%.

[0042] Comparative Examples: To further illustrate the synergistic effect of the combined process of the present invention, the following comparative examples were set up: Comparative Example 1 omits microwaves and only uses ultrasonic-ozone microbubble treatment; Comparative Example 2 does not perform synergistic deep purification, but directly acid leaching and reconstruction; Comparative Example 3 retains the purification and reconstruction steps, but replaces gas-phase permeation pyrolysis with direct mixing and heat treatment of the precursor and solid phosphorus source. Other conditions in the comparative examples are the same as in Example 1.

[0043] The materials and three-electrode catalytic performance of the embodiments and comparative examples of the present invention are shown in Table 1.

[0044] Table 1: .

[0045] Table 2 shows a comparison of the stability of the two-electrode total water splitting process of the present invention with that of the comparative example. Table 2: .

[0046] As shown in Tables 1 and 2, the removal of the organic capping layer and Li leaching both decreased significantly in the absence of microwaves, while the overpotentials of the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) increased, the Tafel slope increased, and C... dl A decrease in / ECSA indicates insufficient reaction kinetics and exposure of active sites. C dl The figure represents the double-layer capacitance, and ECSA represents the electrochemical active area. Without deep purification, PVDF and fluorine residues lead to particle agglomeration, hindered leaching, and decreased catalytic performance, with a larger voltage increment and lower constant-voltage current density retention rate in the constant-flow tank. When solid-phase mixed phosphating is used, although the pre-purification and leaching effects are similar, the active phase particle size is significantly increased, and the OER performance, HER performance, and the stability of both electrodes are all deteriorated. The above results indicate that there is a continuously amplified synergistic relationship among the microwave-ultrasound-ozone microbubble synergistic deep purification, controllable elemental leaching and structural reconstruction, and gas-phase permeation pyrolysis and directional conversion of the present invention.

[0047] The above description is merely one embodiment of the present invention and is not intended to limit the present invention. Any minor modifications, equivalent substitutions, and improvements made to the above embodiment based on the technical essence of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing an electrolytic water catalyst by mixing black powder, characterized in that, Includes the following steps: S1. Mix the black powder with water to form a slurry, and then perform microwave-ultrasound-ozone microbubble synergistic deep purification to obtain purified powder that retains the graphite carbon skeleton and the target metal. S2. The purified powder is subjected to controllable leaching of the target elements in a controllable acid system, and then solid-liquid separation is performed to obtain a solid phase containing a graphite carbon skeleton and a leachate containing lithium ions and transition metal ions, respectively. S3. The solid phase containing the graphite carbon skeleton is returned to the leaching solution or the transition metal enriched portion obtained by the leaching solution through regulation, and in-situ structural reconstruction is carried out to form a composite precursor supported by the graphite carbon skeleton; and lithium salt is recovered from the lithium-containing mother liquor after the composite precursor is separated. S4. The composite precursor is placed in an inert atmosphere for pyrolysis, and at least one of pyrolytic carbonization, metal phosphating and sulfidation occurs, as well as heteroatom doping of the graphite carbon framework, to obtain an electrolytic water catalyst with heteroatom-doped graphite carbon framework supporting multi-metal compounds.

2. The method for preparing an electrolytic water catalyst by mixing black powder according to claim 1, characterized in that, In S1, the mixed black powder is a mixture of positive and negative electrode active materials obtained from waste lithium-ion batteries through discharge, dismantling, crushing and sorting, including at least one of lithium iron phosphate system black powder, ternary system black powder, lithium cobalt oxide system black powder and lithium manganese oxide system black powder. The process of microwave-ultrasound-ozone microbubble synergistic deep purification is as follows: the mixed black powder obtained by crushing and sieving is dispersed in water, and under the simultaneous action of microwave bulk heating, ultrasonic cavitation stripping and ozone microbubble strong oxidation mass transfer, the polyvinylidene fluoride binder, residual electrolyte, SEI membrane and CEI membrane components, fluorine-containing organic derivatives, membrane fibers and fine impurities attached to aluminum foil and copper foil on the surface of the mixed black powder are removed, and purified powder retaining the graphite carbon skeleton and one or more target elements of Fe, Ni, Co, Mn and P is obtained.

3. The method for preparing an electrolytic water catalyst by mixing black powder according to claim 2, characterized in that, In S1, black powder and water are mixed in a mass-volume solid-liquid ratio of 1g:(10-30)mL to form a slurry; In the synergistic deep purification process of microwave-ultrasound-ozone microbubble, the microwave power is 300W-800W, and it operates in continuous or pulsed mode; the average diameter of the ozone microbubbles is no greater than 50 mm. The ozone concentration was 50 mg / L-120 mg / L; the ultrasonic frequency was 20 kHz-40 kHz; the ultrasonic power was 100 W-500 W; the reaction temperature was 60 ℃-120 ℃; the reaction time was 0.5 h-2 h; and the redox potential of the system was controlled at 700 mV-1100 mV. In this process, ozone microbubbles enter the slurry from the bottom of the reactor. An ultrasonic probe, used for ultrasonic treatment, is positioned below the slurry surface and overlaps with the rising area of ​​the ozone microbubbles. Microwave radiation selectively heats the organic-coated particles in the slurry. The foamy light phase and cleaning fluid formed during the purification process carry PVDF-decomposed small molecules... Hydrolysis and oxidation products, membrane fibers, and aluminum and copper particles are discharged, thereby reducing mass transfer resistance in subsequent leaching and remodeling steps.

4. The method for preparing an electrolytic water catalyst by mixing black powder according to claim 3, characterized in that, In S2, the controllable acid system is sulfuric acid, hydrochloric acid, nitric acid, citric acid, oxalic acid, malic acid, or a mixture of the above acids, with an acid concentration of 0.2 mol / L-1.5 mol / L, and the leaching temperature is... The leaching time is 0.5h-2h, and the pH at the leaching endpoint is 1.5-2.

5. The controlled leaching using a controllable acid system ensures that the proportion of lithium ions entering the liquid phase is not less than 90%, and the retention rate of the graphite carbon skeleton is not less than 80%. The transition metal ions included in the leaching process are lithium ions and transition metal ions, including one or more of Fe, Ni, Co, and Mn.

5. The method for preparing an electrolytic water catalyst by mixing black powder according to claim 4, characterized in that, S3 specifically involves: returning the solid phase containing the graphite carbon framework obtained in step S2 to the leachate or the transition metal enrichment portion; the transition metal enrichment portion is: a liquid phase or wet precipitate phase in which one or more ions of Fe, Ni, Co, and Mn are relatively enriched, obtained from the leachate by adjusting the pH to 4.5-8.5, adding a complexing agent, adding a precipitant, ion exchange, or electrochemical enrichment. After the recombination is completed, nitrogen-containing ligands, sulfur-containing ligands and structure-directing agents are added to enable transition metal species to grow in situ on the surface and pores of the graphite carbon framework as metal-organic frameworks, layered double hydroxides, metal hydroxides, metal phosphates or their complex precursors. Lithium carbonate can be recovered by adding sodium carbonate, sodium bicarbonate, ammonium carbonate, or introducing carbon dioxide to the lithium-containing mother liquor after separating the composite precursor for carbonization precipitation.

6. The method for preparing an electrolytic water catalyst by mixing black powder according to claim 5, characterized in that, The nitrogen-containing ligand is one or more of 2-methylimidazolium, urea, melamine, dicyandiamide, or polyvinylpyrrolidone; the sulfur-containing ligand is one or more of thiourea, thioacetamide, p-aminobenzenesulfonic acid, or dibenzyl disulfide; the structure-directing agent is one or more of hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, polyvinylpyrrolidone, polyethylene glycol, polyethyleneimine, Pluronic F127, Pluronic P123, citric acid, or sodium citrate; the structure-directing agent is used to regulate the nucleation density, lamellar orientation, particle size, or porous shell structure of transition metal species on the surface and within the pores of the graphite carbon framework; the structure reconstruction temperature is 120℃-180℃, and the time is 6h-24h, so that the metal species grow in situ on the surface and within the pores of the graphite carbon framework in the form of nanosheets, nanoparticles, or porous shells.

7. The method for preparing an electrolytic water catalyst by mixing black powder according to claim 6, characterized in that, S4 specifically involves: pyrolyzing the composite precursor formed by in-situ structural reconstruction in an inert atmosphere; simultaneously, generating a phosphorus-containing gas phase by independently heating at least one of sodium hypophosphite, triphenylphosphine, and red phosphorus, and / or generating a sulfur-containing gas phase by independently heating sulfur powder, thiourea, or an organic sulfur source, and using a carrier gas to permeate the phosphorus-containing gas phase and / or sulfur-containing gas phase through the composite precursor, causing the composite precursor to undergo carbonization and at least one of phosphating and sulfidation, while simultaneously doping with at least one heteroatom of N, S, and P, forming nano-multi-element metal phosphides, metal sulfides, metal oxides, and composite phases formed by at least two of metal oxides, metal sulfides, and metal phosphides, and uniformly loading the active phase onto the graphite carbon framework; The pyrolysis temperature is 700℃~900℃, the heating rate is 2℃ / min~10℃ / min, the holding time is 1h~4h, the carrier gas is argon or nitrogen, and the flow rate is 30mL / min~200mL / min.

8. A water electrolysis catalyst prepared by the method for preparing an electrolysis catalyst from mixed black powder according to any one of claims 1-7, characterized in that, A carbon network containing at least one heteroatom doped with N, S, or P, and an active phase loaded on the carbon network; The active phase is one of metal phosphides, metal sulfides, and metal oxides, or a composite phase formed from at least two of metal phosphides, metal sulfides, and metal oxides; the metal phosphides include... , or Metal sulfides include , or The average particle size of the active phase is 5nm-30nm, and at least part of the active phase is coated with 1-5 layers of graphitized carbon shell.

9. A preparation system for implementing the method of preparing an electrolytic water catalyst from mixed black powder as described in claim 1, characterized in that, It includes a purification unit, a first solid-liquid separation unit, a selective leaching-structure reconstruction unit, a second solid-liquid separation unit, a gas phase permeation pyrolysis unit, and a tail gas absorption unit connected in sequence, and includes a control unit connected to each of the above units; The purification unit includes a reactor (5) with temperature control function, and a microwave emitting device (1) is provided on the side of the reactor (5); a temperature controller (7) is provided on the side wall of the reactor (5), an outlet (6) of the reactor (5) is provided above the temperature controller (7), and an inlet (8) of the reactor (5) is provided below the temperature controller (7); an oxidation-reduction potential detection device is provided inside the reactor (5), an ultrasonic probe (4) is provided on the top cover of the reactor (5) and extends vertically into the reaction chamber, and a bubble outlet (9) with a shower structure and an upward-facing outlet is provided at the bottom of the reactor (5). The bubble outlet (9) is sequentially connected to the microbubble generator (3) and the ozone generator (2) through pipelines; wherein the end position of the ultrasonic probe (4) overlaps with the rising area of ​​the ozone microbubbles generated by the bubble outlet (9); The gas-phase permeation pyrolysis unit includes a furnace body, a heat-resistant reaction tube penetrating the furnace body, a carrier gas inlet, a gas phase source zone located upstream of the carrier gas, a precursor pyrolysis zone located downstream of the gas phase source zone, a furnace temperature control unit, and a condensation absorption zone connected to the outlet of the heat-resistant reaction tube; the gas phase source zone, the precursor pyrolysis zone, and the condensation absorption zone are connected sequentially along the direction of carrier gas flow.

10. The preparation system according to claim 9, characterized in that, The solid phase outlet of the first solid-liquid separation unit is connected to the selective leaching-structural reconstruction unit, the liquid phase outlet of the second solid-liquid separation unit is connected to the lithium salt recovery unit, and the solid phase outlet of the second solid-liquid separation unit is connected to the gas phase permeation pyrolysis unit; the control unit controls the microwave power, ultrasonic power, ozone flow rate, pH, redox potential, acid leaching endpoint, carrier gas flow rate, and pyrolysis temperature in a coordinated manner.